"Porous and Yet Dense" Electrodes for High‐Volumetric‐Performance Electrochemical Capacitors: Principles, Advances, and Challenges. Issue 4 (18th November 2021) - Pan, Zhenghui; Yang, Jie; Kong, Junhua; Loh, Xian Jun; Wang, John; Liu, Zhaolin
Abstract: With the ever‐rapid miniaturization of portable, wearable electronics and Internet of Things, the volumetric performance is becoming a much more pertinent figure‐of‐merit than the conventionally used gravimetric parameters to evaluate the charge‐storage capacity of electrochemical capacitors (ECs). Thus, it is essential to design the ECs that can store as much energy as possible within a limited space. As the most critical component in ECs, "porous and yet dense" electrodes with large ion‐accessible surface area and optimal packing density are crucial to realize desired high volumetric performance, which have demonstrated to be rather challenging. In this review, the principles and fundamentals of ECs are first observed, focusing on the key understandings of the different charge storage mechanisms in porous electrodes. The recent and latest advances in high‐volumetric‐performance ECs, developed by the rational design and fabrication of "porous and yet dense" electrodes are then examined. Particular emphasis of discussions then concentrates on the key factors impacting the volumetric performance of porous carbon‐based electrodes. Finally, the currently faced challenges, further perspectives and opportunities on those purposely engineered porous electrodes for high‐volumetric‐performance EC are presented, aiming at providing a set of guidelines for further design of the next‐generation energy storage devices. Abstract : "Porous and yet dense" electrodes with optimum structures that balance the level of porosity and packing density are crucial to realize high‐volumetric‐performance electrochemical capacitors. This review presents design principles, recent achievements, and further perspectives on "porous and yet dense" electrodes, aiming at providing a set of guidelines for development of the nextgeneration advanced electrochemical capacitors.